Toward Molecular Level of the “Salmonella-Victim” Ecology, Genetics, and Evolution - S.N. Rumyantsev (The Scientific World Journal)
Bacteria of the Salmonella genus are polypathogenic agents that can affect both men and animals, causing devastating and fatal illness. Despite considerable immunological, epidemiological, and genetic efforts, and increased understanding of how the Salmonella infection develops, many key questions concerning Salmonella infection remain unanswered. Salmonella can be carried as harmless commensals in some sectors of the population. In some individuals, however, the same microbes cause illness while others display immunity to primary Salmonella infection. Nothing is known about the molecular base of the Salmonella pathogenicity. Even the ability of Salmonella to destroy the victims cells has been the subject of century-long discussions. In this article, some key findings concerning ecology, molecular ecology, and cell level of the Salmonella infection genetics are summarized and interpreted from the viewpoint of evolutionary theory with certitude that this approach can help to decipher the undiscovered secrets of Salmonella infections epidemiology and pathogenesis, as well as the clinical course and severity, and to select ways for fighting against Salmonella.